2018
DOI: 10.1111/irj.12211
|View full text |Cite
|
Sign up to set email alerts
|

The non‐professionally affiliated (NPA) worker as co‐producer of public services: how is the role experienced in UK mental health services?

Abstract: Recent workforce reforms have led to the widespread expansion of non‐professionally affiliated (NPA) support and assistant roles within UK public services. Research into these roles has been confined to a limited range of settings, with a focus on the consequence of change for professional workers. This article explores the emergence of ‘co‐production’, whereby NPA workers contribute alongside the professional in a distinct, complementary way. Findings are drawn from semi‐structured interviews with frontline w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The article's framework also resonates with the workforce innovation literature's emphasis on complementarity, and indeed advances this field by putting a stronger emphasis on managerial facilitation. Workforce innovation studies often examine managerial interventions that allocate some of an established profession's tasks to a lower‐skilled role such as, for example, healthcare assistants (Chen et al., 2022; Kessler et al., 2015; Krachler & Kessler, 2022; Procter et al., 2018). While these studies acknowledge the role of managerial facilitation, they emphasize the autonomous regulation of occupational relations over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The article's framework also resonates with the workforce innovation literature's emphasis on complementarity, and indeed advances this field by putting a stronger emphasis on managerial facilitation. Workforce innovation studies often examine managerial interventions that allocate some of an established profession's tasks to a lower‐skilled role such as, for example, healthcare assistants (Chen et al., 2022; Kessler et al., 2015; Krachler & Kessler, 2022; Procter et al., 2018). While these studies acknowledge the role of managerial facilitation, they emphasize the autonomous regulation of occupational relations over time.…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to 'substitution', where the new role performs tasks that are traditionally in the established professionals' domain for a lower cost, 'complementarity' develops when new roles assume tasks that were not previously performed or are considered 'lower-status', thus 'freeing up' professionals to perform higher-status tasks (Bach et al, 2008;Kessler et al, 2015Kessler et al, , 2017. While these processes could occur without managerial intervention, these studies found that HR practices such as training, mentorship, autonomy (Chen et al, 2022), multi-disciplinary teamworking, and assigning manageable workloads (Procter et al, 2018) could facilitate cross-occupational working.…”
Section: Nascent Research On Hpwp Implementation Conditionsmentioning
confidence: 99%
“…Other studies have highlighted the increasingly active role of managerial supports like career structures (Bach et al., 2008). For example, Procter and colleagues (2018) argued that managers’ use of team structures and workload assignment facilitated joint working between professional mental health staff and lower‐skilled, mental health assistants. Similarly, Krachler and Kessler (2023) documented how primary care physicians in England used managerial control practices (e.g.…”
Section: Perspectives On New Work Rolesmentioning
confidence: 99%
“…This article opens up two areas for further research. First, while this novel study examined a process of new task creation through a new role, most research in this area concerns the reallocation of existing tasks from an established occupation to a new role (Kessler et al., 2013; Procter et al., 2018). Therefore, further research could study the applicability of institutional supports to such cases of task reallocation as well.…”
Section: Implications For Theory and Policymentioning
confidence: 99%